A Case of Child Physical Abuse With a Rolling Pin Insertion, Resulting in Bladder and Rectal Perforation. Issue 3 (March 2018) - Kondolot, Meda; Doganay, Selim; Turan, Cüneyt; Asil, Hasim; Oztop, Didem B.; Ozdemir, Caglar
Abstract : Abstract: Visceral injuries are not uncommon in nonaccidental trauma and often require emergent operative intervention. However, sometimes it can be difficult to assess the extent of injury. In this report, we present a case of child physical abuse resulting in bladder and rectal perforations, which was initially referred to our hospital as acute abdomen with intraperitoneal free fluid on ultrasonography. An exploratory laparotomy revealed the perforations and surgical repair was performed. The patient was evaluated by the Hospital Child Protective team and it was revealed that bladder and rectum perforations were due to insertion of rolling pin into the rectum by the stepmother. The child was discharged home uneventfully with a temporary colostomy. We believe that this is the first reported case in the English literature of inflicted perforation of the rectum and bladder through insertion of a rolling pin.